Thyroid disorders in Bangladesh- Past, Present and Future - Ansari, Md Abdul Jalil (Journal of Dhaka Medical College, 2015)
Abstract not available J Dhaka Medical College, Vol. 23, No.2, October, 2014, Page 151-152